การบริหารจัดการการเรียนรู้ชุมชนเพื่อประกอบสัมมาชีพ องค์การบริหารส่วนตำบลหนองเหล็ก อำเภอโกสุมพิสัย จังหวัดมหาสารคาม Administration of Community Learning for Taking up Right Occupations in Nong Lek Tambon Administration Organization, Kosum Phisai Distr - หวานขม, พรปวีณ์; วงศ์เกษม, สมชาย; แก้วคำ, สุทัศน์ (Chophayom Journal, 2016)
บทคัดย่อ กการวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพการเรียนรู้ในชุมชนเพื่อการประกอบสัมมาชีพ 2) แนวทางในการบริหารจัดการพัฒนาศักยภาพการเรียนรู้ในชุมชนเพื่อประกอบสัมมาชีพ องค์การบริหารส่วนตำบลหนองเหล็ก อำเภอโกสุมพิสัย จังหวัดมหาสารคาม โดยใช้วิธีวิจัยเชิงปฏิบัติการ (Action Research) ประกอบด้วย 4 ขั้นตอน คือ การวางแผน การลงมือปฏิบัติ การสังเกต และการสะท้อนผล โดยใช้การประชุม และการอบรมเชิงปฏิบัติการ ซึ่งมีกลุ่มผู้ร่วมวิจัย จำนวน 7 คน ได้แก่ ผู้บริหารและพนักงานส่วนตำบลหนองเหล็ก ผู้ให้ข้อมูล จำนวน 40 คน ได้แก่ ประธานและกรรมการกลุ่มอาชีพ 4 กลุ่ม กลุ่มละ 10 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล ได้แก่ แบบสังเกต แบบสัมภาษณ์ และแบบสอบถาม วิเคราะห์ข้อมูลเชิงปริมาณโดยใช้สถิติค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน และนำเสนอข้อมูลด้วยตารางและการพรรณนาวิเคราะห์ กกกกกกกผลการวิจัยพบว่า กกกกกกกกก 1) ปัญหาสภาพการจัดการเรียนรู้ในชุมชน พบว่า (1) ขาดแหล่งเรียนรู้ชุมชน (2) ไม่ได้ประกอบอาชีพเสริมในครัวเรือนหลังฤดูทำนา และ (3) ปัญหาการว่างงาน 2) ผลการศึกษาแนวทางในการบริหารจัดการพัฒนาศักยภาพการเรียนรู้ในชุมชนเพื่อการประกอบสัมมาชีพ ตามการวิจัยเชิงปฏิบัติการ ได้แก่ (1) การวางแผนเขียนโครงการอบรมเชิงปฏิบัติการ (2) การปฏิบัติกิจกรรมโดยการอบรมความรู้ด้านสัมมาอาชีพตรงกับความต้องการของประชาชน (3) ผลการสังเกตผู้เข้าร่วมการอบรมความรู้มีความตั้งใจที่จะพัฒนาตนเอง และให้ความร่วมมือในการดำเนินกิจกรรมต่าง ๆ ตามเวลาที่กำหนด มีความพึงพอใจต่อการมีส่วนร่วมในการบริหารจัดการการเรียนรู้ชุมชน ความรู้ที่ได้จากการเรียนรู้ไปใช้ในการสร้างความรู้ใหม่เพื่อประกอบอาชีพเสริมในครัวเรือนแก้ปัญหาการว่างงาน และ (4) การสะท้อนผลการจัดกิจกรรมอบรมเชิงปฏิบัติการกลุ่มเป้าหมายและกลุ่มผู้ร่วมวิจัยเข้าใจในการบริหารจัดการกิจกรรมการอบรมเชิงปฏิบัติการ มีการวางแผนการบริหารจัดการการเรียนรู้ ดำเนินการบริหารจัดการเรียนรู้ วัดผล ประเมินผลการบริหารจัดการ และมีการปรับปรุงการบริหารจัดการการเรียนรู้ โดยรวมอยู่ในระดับ มาก คำสำคัญ: การบริหารจัดการเรียนรู้ชุมชน Abstract The research aimed to 1) study the state of learning in the community for taking up right occupations; 2) study the means of administering the development of learning potentiality in the community for taking up right occupations in Nong Lek Tambon Administration Organization, Kosum Phisai District, Maha Sarakham Province by using action research methodology which comprises 4 steps: planning, action, observation, and reflection. Meetings and workshop were used. The research group comprised 7 persons who were administrators and officers of Nong Lek Tambon Administration Organization. The informants consisted of 40 persons who were the chairpersons and committee members of 4 occupational groups of 10. The instruments used in the collection of data comprised an observation form, an interview form, and a questionnaire. The quantitative data were analyzed by using percentage, mean, and standard deviation. The data were presented in tables and a descriptive analysis. กกกกกกThe results are as follows: 1) Regarding the problems of learning organization in the community, it was found that (1) there was a lack of learning sources; (2) the people did not take up household supplementary occupations after the planting season, and (3) unemployment. The results of the study on the means of administering the development of learning potentiality of learning in the community for taking up right occupations, according to the action research which included the following activities: (1) planning for writing a workshop project; (2) carrying out the activity of imparting the knowledge of the right occupations as needed by the people; (3) the observation on the trainees revealed their intention of self-development, and they cooperated in carrying out activities as scheduled. They were satisfied with the participation in the administration of learning in the community as well as using the knowledge they had learned in building new knowledge for taking up supplementary occupations in the households to solve the unemployment problem; and (4) the reflection of carrying out activities in the workshop revealed that the research group understood the administration of the workshop activities. There was planning of learning administration, taking the action of learning administration, measuring and evaluating of learning administration and there was improvement of learning administration, on the whole, in the high level. Keyword: Administration of Community Learning